O ato de dar nome ao bebê: um recorte sobre a constituição psíquica dos bebês internados em uma Unidade de Terapia Intensiva Neonatal - ESPÍNDOLA, Vanessa Barros (2017)
The dissertation aimed at discussing a baby's passage through a Neonatal Intensive Care Unit (NICU), taking the concept of proper name as the point of guiding the construction of writing. For that, the theory of significant was used, just as Jacques Lacan left us. While a theoretical research, a dissertation was based on the psychoanalytical method that presents as main characteristic the questions formulation’s mode, not seeking for generalizations or considerations and considering that, in the field of investigations, the researcher also suffers the question’s effect and what comes from them. As Psychoanalysis is theory produced by practice, the discussion is permeated by cuts of work done in NICU with the babies and their families. This practice was based on the speech of the subjects that circulated in the neonatal environment, working with the aspects involved in being born, getting sick, dying, healing, and to the act of naming the babies there. The child has his condition of life in the words of which it is addressed and overdetermined by signifiers, which give his speaking dimension. A subject is constituted by a language operation and the signifier shows that unconscious is structured as a language. The name stands as a mark that singles out the speaking being, its anchoring point, its place in the world. It is a talking being, coming from a lack that structure, which Psychoanalysis is intended. The passage through the NICU has effects on the act of naming the infant. During the hospitalization’s time, the changes in names are common. Such changes show the place given to the child in the desire of the parents. Desire that is the pass for the subject to come into the world, as the one that denotes a functioning that extrapolates the consciousness, figuring as an interval in the significant pair. The subject is only alienated to the desire of the Other, figuring as the object of his desire, and has in his name a mooring point of his constitution. The name allows the child an inscription, a progeny, a place in the culture, a bet of life or death.